Effect of the Knee and Hip Angles on Knee Extensor Torque: Neural, Architectural, and Mechanical Considerations - Garnier, Yoann M.; Lepers, Romuald; Canepa, Patrizio; Martin, Alain; Paizis, Christos (Frontiers in Physiology, 2022)
This study examined the influence of knee extensors’ hip and knee angle on force production capacity and their neuromuscular and architectural consequences. Sixteen healthy men performed submaximal and maximal voluntary isometric contractions (MVIC) of knee extensors with four different combinations of the knee and hip angles. Muscle architecture, neuromuscular function, and corticospinal excitability were evaluated on the vastus lateralis (VL) and rectus femoris (RF) muscles. MVIC and evoked peak twitch (Pt) of knee extensors decreased significantly (p < 0.05) by 42 ± 12% and 47 ± 16% on average respectively under knee extended positions (20° flexion, 0° = full extension) compared to knee flexed positions (110° flexion), but were unaffected by hip angulation. Increasing knee flexion from 20° to 110° increased significantly (p < 0.05) VL and RF muscle and fascicle lengths but did not change muscle activation. Significant reduction (p < 0.05) in pennation angle of the VL muscle occurred in knee-flexed position and hip extended positions. Decrease in pennation angle (p < 0.05) occurred for the RF muscle in a knee-flexed position. MVIC of knee extensors depended particularly upon peripheral contractile elements such as VL and RF muscle and fascicle lengths but was unaffected by central factors (i.e., muscle activation). Furthermore, the hip position can affect the pennation angle of the VL, while VL muscle length can affect the pennation angle of the RF muscle. These elements suggest that the VL and RF muscles exert a mutual influence on their architecture probably related to the rectus-vastus aponeurosis.